Optimization of wireless power transmission for two-port and three-port inductive link - Haider, Samnan; Mansor, Hasmah; Khan, Sheroz (IOP Publishing, 2013)
Recent developments have shown that the use of buried electronic devices or body implants has been becoming prevalent. Such low power devices are being powered up through non-contact means utilizing inductive coupling from external powering source. Inductive coupling not only solves the issue of energy availability but helps collecting the sensed data that can be archived or used for subsequent monitoring purposes. This paper analyses the performance of two-port and three-port inductive links in terms of power sent, power received and power transfer efficiency. All the above mentioned parameters have been plotted using analytical approach and obtaining simulation where required. The effect of mutual coupling has been studied in detail for both systems and demonstrated by plotting the power transfer efficiency for different values of the coefficient of coupling (k) using MATLAB. Results show that power transfer efficiency depends highly upon the value of k.